2022
DOI: 10.3390/land11030323
|View full text |Cite
|
Sign up to set email alerts
|

Ageing Perception as a Key Predictor of Self-Rated Health by Rural Older People—A Study with Gender and Inclusive Perspectives

Abstract: This paper investigates positive perceptions of ageing in rural people aged 65 and over as a key predictor of the self-assessment of one’s health. Method: The sample covers a total of 3389 people from the ‘Survey of Health, Ageing and Retirement’ (SHARE), wave 6 (W6, 2015). This research analyses men and women who live in a rural environment. A linear regression model is proposed to consider the dependent variable ‘self-rated health’ and independent variables based on measures of quality of life in older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Moreover, the differences in the location and layout of different types of service facilities for older people need to be further explored [39]. In addition to the issue of facility distribution, the impact of individual preferences, gender differences, and other subjective perspectives on service facilities for older people is a direction worth considering for future research [55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the differences in the location and layout of different types of service facilities for older people need to be further explored [39]. In addition to the issue of facility distribution, the impact of individual preferences, gender differences, and other subjective perspectives on service facilities for older people is a direction worth considering for future research [55].…”
Section: Discussionmentioning
confidence: 99%
“…One thing that might be explained is related to the perception that is followed by health behavior from the side of the individual woman. Women who live less healthy lives than men are more likely to take advantage of the hospital, although biologically, women generally live longer than men [ 1 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following this, a previous study in 2022 conducted in Bangladesh observed that abusive relationships towards dependent older people have emerged as a consequence of parental culture differentiation, including the dissociation of the family system, the deterioration of ethical values, the disrespect for the helpless and elderly, the prevalent use of dowry, increased rates of divorce, the rise in growing requirements on family members, the development of a self-centered attitude, and an increase in conflict in both marital and family life [15]. Moreover, the results from the current study show that almost 30% 60-65 aged population experience no abusive behavior due to health-related spending as they are more active and productive than other age groups (Figure 3).…”
Section: Abusive Relationshipmentioning
confidence: 99%